2015
DOI: 10.1590/s0080-623420150000700022
|View full text |Cite
|
Sign up to set email alerts
|

Segurança do paciente em Unidades de Terapia Intensiva: desenvolvimento de um projeto de pesquisa

Abstract: RESUMO Objetivo Relatar a experiência sobre os diferentes processos envolvidos no desenvolvimento de um Projeto de Pesquisa em Segurança do Paciente em Unidades de Terapia Intensiva. Método Estudo com delineamento misto: coorte histórica para a coleta dos dados dos pacientes e eventos adversos/incidentes e transversal para a coleta dos dados da equipe de enfermagem. A coleta de dados ocorreu durante 90 dias, em 2012, no Instituto Central do Hospital das Clínicas da Universidade de São Paulo e o Hospital Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
(14 reference statements)
0
8
0
6
Order By: Relevance
“…The association between the environment of nursing practices and work satisfaction has been investigated in recent years, showing that the characteristics of the environment influence the results of work satisfaction and nursing care practices in the ICU (1)(2)(3)(4)(5)(6)10) . The results of the present study showed that the nursing team is predominantly female (83.97%), a characteristic of this profession, which has also been observed in other studies (2,6,(10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the environment of nursing practices and work satisfaction has been investigated in recent years, showing that the characteristics of the environment influence the results of work satisfaction and nursing care practices in the ICU (1)(2)(3)(4)(5)(6)10) . The results of the present study showed that the nursing team is predominantly female (83.97%), a characteristic of this profession, which has also been observed in other studies (2,6,(10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
“…This study originated from the Universal Project and doctoral thesis (4) , conducted with the nursing team of eight ICUs of a public university hospital with capacity for approximately 900 beds, 100 of which were distributed among Intensive Care Units of the following specialties: Emergency Room of Clinical Emergencies, Emergency Room of Surgical Emergencies, Internal Medicine/Pulmonology, Infectious Diseases, General Surgery, Neurology, Nephrology and Burned Victims.…”
Section: Study Design Setting and Periodmentioning
confidence: 99%
“…(7,9) The national level is characterized by the epidemiology of adverse events and their relationship with patient severity, comorbidities, nursing workload, length of stay and reason for hospitalization. (6,(9)(10)(11)(13)(14)(15)(16) Nursing workload and length of stay are factors associated with the occurrence of adverse events. (6) However, specific data related to elderly people are scarce and the factors associated with patient safety incidents are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9]12 It is related to the occurrence of AE with more severe damage to Intensive Care Units (ICUs), operating rooms and emergencies [5][6][7] and, in relation to the ICU, there is a greater vulnerability to care failures compared to other units due to their seriously ill patients, the requirement for complex intensive care, the longer the hospital stay, the different health professionals for the care and expertise needed to handle various technologies. 13 In relation to the multidisciplinary care of the critical patient, the nursing team is the largest staff responsible for care actions, therefore, in a privileged position to reduce the possibility of failures that affect the patient. It is pointed out that, in addition to detecting complications early, it can perform the necessary conducts to minimize damage.…”
mentioning
confidence: 99%
“…It is pointed out that, in addition to detecting complications early, it can perform the necessary conducts to minimize damage. 13 Some aspects in Nursing are pointed out as probable risk factors associated with AE, for example: higher workload, stress, burnout, characteristics of the profession, the environment of Nursing practices, professional satisfaction and their perception of safety culture. It is necessary to deepen the subject in the face of evident efforts in the detection of fragilities related to patient safety, the importance of monitoring the AEs, the methodologies, often costly, with limited sensitivity or low efficiency.…”
mentioning
confidence: 99%